Four Additional Meroterpenes Produced by Penicillium sp Found in Association with Melia azedarach. Possible Biosynthetic Intermediates to Austin - Taícia Pacheco Fill; Grace Kelli Pereira; Regina M. Geris dos Santos; Edson Rodrigues‐Fo (2007)
Four additional meroterpenes were isolated and identified from rice cultures of Penicillium sp, a fungus obtained from the root bark of Melia azedarach. These new compounds were named preaustinoid B2 (1), preaustinoid A3 (2), austinolide (3), and isoaustinone (4) in analogy with the formerly described compounds. The structures were identified by extensive spectroscopic studies, including 1 D and 2 D NMR spectroscopy and HRMS. Compounds 1 - 4 are probably biosynthetic intermediates to Austin.